Acute onset olfactory/taste disorders are associated with a high viral burden in mild or asymptomatic SARS-CoV-2 infections. (October 2020) - Nakagawara, Kensuke; Masaki, Katsunori; Uwamino, Yoshifumi; Kabata, Hiroki; Uchida, Sho; Uno, Shunsuke; Asakura, Takanori; Funakoshi, Takeru; Kanzaki, Sho; Ishii, Makoto; Hasegawa, Naoki; Fukunaga, Koichi; et al.
Highlights: Cycle threshold values were associated with the time to negative qPCR of SARS-CoV-2. Olfactory and taste disorders occurred after development of fever and sore throat. Fever and olfactory and taste disorders were correlated with higher viral burden. Assessment of olfactory and taste disorders may be important to prevent transmission. Abstract: This study investigated, using cycle threshold (Ct) qPCR values, the association between symptoms and viral clearance in 57 patients with asymptomatic/mild SARS-CoV-2 infection. Patients with olfactory/taste disorders (OTDs) exhibited lower qPCR Ct values and longer time to negative qPCR than those without OTDs, suggesting an association between OTDs and high viral burden.